Implementasi Program Toilet Training Dalam Menumbuhkan Kemandirian Anak Usia Toddler Di Kelompok Bermain - Inayah Nurbaiti; Retno Wulandari; Fahmi Fahmi (Childhood Education : Jurnal Pendidikan Anak Usia Dini, 2024)
Toilet training young children is an essential milestone in a child's journey towards independence. This study explored the implementation and outcomes of a structured toilet training program in a playgroup setting. The aim is to assess its effectiveness in fostering independence in toddlers aged 1.5 to 3 years. The program takes a gradual approach, emphasizing positive reinforcement and consistency in the routine. This research uses a qualitative approach with a case study type of research. The data collection techniques used included observations of participating toddlers over six months, with data collected through interviews with teachers and direct observation during playgroup activities. The data analysis technique used is Miles and Huberman. The research results showed that, first, in the Al-Fatih KB, 5 of the 14 children had difficulty using the toilet. Second, teachers' structured and consistent approach has proven effective in helping children understand and internalize toilet use skills. Third, the supporting factors in training children's independence in using toddler toilets at Al-Fatih KB Palembang City include good cooperation between teachers and parents, mental and psychological readiness of children, mature age, and complete and adequate facilities and infrastructure in Toilet Training learning. Meanwhile, the inhibiting factors include the child's age, mental and psychological not being ready to learn Toilet Training and the lack of cooperation from parents who still use disposable diapers on their children.